Факторизації і симетрична еквівалентність матриць над кільцем многочленів з інволюцією - Кучма, М. І.; Kuchma, M. I. (Видавництво Львівської політехніки, 2017)
Встановлено необхiднi й достатнi умови iснування факторизацiї симетричних матриць, якi си- метрично еквiвалентнi до форм Смiта, над кiльцем многочленiв з iнволюцiєю. Отримано критерiй ∇-конгруентностi симетричних матричних двочленiв.

We establish necessary and sufficient conditions for the existence of factorization of symmetric matrices that symmetric equaivalent to the Smith forms over ring of polynomials with involution. The criterion of ∇-congruence symmetric matrix binomials is obtained.
Factorizations and symmetric equivalence of matrices over polynomial ring with involution
Keywords: симетрично еквівалентні матриці; ∇-конгруентні матриці; факторизація матриці; symmetric equaivalent matrices; ∇-congruent matrices; factorization of matrix; 512.64